SI- MASPRO LEARNING MEDIA TO IMPROVE STUDENTS' SELF-REGULATED AND LEARNING OUTCOME DURING THE COVID-19 PANDEMIC - Agata Sari, Cornelia (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
Enactment policy Distance Learning ( PJJ) for disconnect eye chain the spread of Covid-19 in Indonesia as well development increasingly technology _ rapidly can used by internal teachers learning that impacts independence and outcomes _ Study participant educate . Besides that is development technology can too used by teachers do learning in the 21st century viz designed lessons _ For print participant educate 21st century that can Work same , do good communication , think _ critical and creative . one _ utilization technology in the learning process that is with using learning media based on android, as participant educate Already No foreign Again with use internal smartphones life everyday . Procedure and development in study This use method research and development Brog and Gall who have modified into 8 stages . Analysis technique virgin used _ that is approach qualitative For analyze criticism and suggestions and approaches quantitative For analyze results validation expert use descriptive presentation and analysis independence as well as results Study participant educate . Research and development results This in the form of learning media based on android named Si- Maspro ( Public Relations and Protocol Application ) which has been declared very valid and feasible used in learning automation of public relations governance and protocol class XII Office Management Automation (OTKP) by experts materials , media experts , and 6 participants try out _ group small . Si- Maspro learning media has proven can increase independence and results Study participant educate after group trials were carried out big . Conclusion of Si- Maspro learning media that is feasible and effective used as a learning medium For increase independence and results Study participant educate the eyes lesson automation of public relations and protocol governance .